Digitalization of historic buildings using modern technologies and tools - Anna Prokop; Piotr Nazarko; Leonard Ziemiański (Budownictwo i Architektura, 2021)
The aim of the paper is to present some experiences of using modern technologies to historical buildings digitalization. The emphasis is placed on the possibilities of spatial data collecting, as well as on subsequent 3D modelling. The paper describes the proposed survey techniques which are based on the Terrestrial Laser Scanning and photogrammetry. The authors obtained the point cloud by using the laser scanner Faro Focus 3D and dedicated software to combine scans (target based and cloud to cloud methods). The paper also provides an introduction to issues related to a method of building structure modelling based on a point cloud. The authors proposed some computer software tools that could improve work with a point cloud and the modelling process. The resulting 3D model could be both a source of information about historical building and a sufficient base to create computational model with spatial finite elements. The subject of the case study is the St. Hubert Chapel located in Rzeszów (Poland) and built in the middle of the 18th century under the patronage of the Lubomirski family. This rococo chapel is one of the most valuable architectural monuments in the region. Historical Building Information Model (HBIM) could be helpful in analysis, visualisations and conservation practice of this precious monument. Diagnosing the current object state and assessing its technical condition could be the purpose of creating a computational FEM model.